Simulation of the impact of Covid-19 outbreak for airport terminal operations at Sam Ratulangi International Airport - Pandiangan, Melania Lidwina (International Journal of Aviation Science and Engineering - AVIA, 2023)
Indonesian airport regulators have taken steps to keep their airports operational during the Covid-19 pandemic. Measures such as implementing physical distance, checking body temperature and checking health documents have affected the efficiency of the airport terminal. Covid-19 Crisis Management has made major operational adjustments. This action has been effectively carried out in situations where passenger transport has been limited due to regulatory agency flight restrictions. However, it is still unclear what the output will be when the demand normalizes. The purpose of this paper is to compare terminal operations before and after the occurrence of Covid-19. This paper evaluates the impact of Covid-19 measures on airport terminal performance using simulation tests of CAST 8 terminal simulation software. The model represents Sam Ratulangi International Airport (IATA: MDC) in Manado, Indonesia. This model covers the departure and the arrival areas. The flight schedule of the selected date taken from the flight radar website generates the passengers, the farewellers, and the meeters. IATA ADRM 11th Edition is the guidelines to determine the level of service. Adjustments for Covid-19 scenarios include number of passengers, physical distance, processing flow, and waiting time. The results show that the waiting time of each process has increased latency and at some point the latency exceeds the optimum service level. The simulation results allow local airport authorities to maintain a specified level of service at MDC airport.